Political environment in the effect of the regional government financial performance on disclosure of financial information on website - Yustina Hiola; Rosidi Rosidi; Aji Dedi Mulawarman (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to analyze the effect of financial performance of local governments towards the disclosure compliance of financial information on the website, as well as the political environment as a moderating variable for the effect of the financial performance of local governments towards disclosure compliance of financial infor-mation on the website. The study was conducted at the local government in Sulawesi with the sample consisting of 53 governments. The data were analyzed by partial least square (PLS). The results showed that good financial performance of local governments can encourage disclosure compliance of financial information on the website. This study also found that the political environment cannot moderate the effect of the financial performance towards the disclosure compliance of financial information on the website. This is due to the people who are interested more in paper-based reporting. The implication of this study was to encourage related re-search as well as encouraging local governments to use website as a media for finan-cial information reporting. Gorontalo district government is local government, which has excellent financial performance with complete disclosure of financial information on the website.